Suggest Mathematical Method for Residential Real Estate Appraisal in Tartous City - جنود, علي; مكية, سماح; سليمان, احمد (Latakia University Journal -Engineering Sciences Series, 2021)
The real estate market in general suffers from a problem in determining the price of residential real estate as residential real estate prices are not subject to controls and are far from their actual market values due to the absence of a specific methodology that helps real estate residents and owners in determining the price of residential real estate in the city of Tartous, so The main aim of this research is to valuate residential real estate prices in tartous city by developing a mathematical model for real estate appraisal using artificial neural networks (ANN) technology. The factors that affect the determination of market value for residential real estate in tartous city were defined by a questionnaire and personal interviews with real estate appraisal experts. Data were collected according to the factors that affect the determination of market value for residential real estate from real estate market in tartous city according to real sales occurring within the boundaries of tartous city during the years (2017-2020). The data were analyzed and processed to build a three layers (input layer - one hidden layer – output layer) neural networks model with 9 different inputs to valuate residential real estate prices in tartous city. The proposed model has a success rate of 85%. The results of this research would help researchers in developing more effective property pricing models in Syria.